Distance Capacity Above the Critical Speed and Speed Reserves: are they Related? - Lanzarini, Lucas Vecchia; Borszcz, Fernando Klitzke; Dalla Lana, Isadora; Turnes, Tiago; Ventura, Thiago Pereira; McGawley, Kerry; de Lucas, Ricardo Dantas (International Journal of Sports Medicine, 2025)
The aim of this study was to correlate the anaerobic speed reserve and the maximal speed reserve with the distance capacity above the critical speed (D′), derived from four different mathematical models, in a group of endurance runners. Twenty-two runners performed an incremental treadmill test to exhaustion, an all-out 40-m sprint and three time trials (800, 1,500 and 3,000 m) on an outdoor running track to determine an anaerobic speed reserve, a maximal speed reserve and D′. D′ was determined using linear distance–time (D′linear d–t), linear velocity–time (D′linear 1/t), 2-parameter hyperbolic (D′2-hyp) and 3-parameter hyperbolic (D′3-hyp) models. A high correlation was observed between the anaerobic speed reserve and D′linear 1/t (r=0.77; p<0.001), while moderate correlations were observed between the anaerobic speed reserve and D′linear d–t (r=0.69; p<0.001) and D′2-hyp (r=0.63; p<0.003). The anaerobic speed reserve was not significantly correlated with D′3-hyp. High correlations were detected between the maximal speed reserve and D′linear 1/t, D′linear d–t and D′2-hyp (r=0.74 to 0.76; p<0.001) and a moderate correlation was detected between the maximal speed reserve and D′3-hyp (r=0.58; p=0.01). These moderate- to high correlations with D′, especially when derived from models using two parameters, suggest the existence of similar mechanisms underpinning the variables.
Keywords: anaerobic capacity; anaerobic speed reserve; D′; maximal speed reserve